What is the evidence linking financial assistance for drought-affected agriculture and resilience in tropical Asia? a systematic review - Goodwin, Daniel; Holman, Ian P.; Pardthaisong, Liwa; Visessri, Supattra; Ekkawatpanit, Chaiwat; Rey Vicario, Dolores (Springer, 2022)
Agriculture is sensitive to drought and associated social, environmental and economic impacts. Finance-based interventions aim to support farmers affected by drought; however, the extent to which such tools encourage resilience to this natural hazard is unclear. This paper systematically reviews evidence on links between financial interventions to mitigate drought-related impacts and adaptation towards longer-term resilience. We focus on tropical Asia where agriculture contributes significantly to national economies and is a primary source of livelihood in a region subject to high climate variability and episodic drought. Guided by Population, Intervention, Comparator and Outcome criteria, we identify and review 43 regionally specific articles that describe a range of financial interventions. Through thematic synthesis, we document the interventions’ associations with micro-level and macro-level outcomes. The results reveal how some interventions helped sustain household incomes and crop yield (e.g. through farm investments that increased productivity) through drought, whilst others encouraged adaptive behaviours. At a macro-level, there were challenges associated with government budgets and scheme administration, with the longevity of many schemes difficult to sustain. From fragmented evidence, this review reasons that there can be challenging policy trade-offs for institutions between supporting livelihoods and economic growth whilst also protecting the environment—highlighting the interdependence of systems’ resilience and variability in actors’ capacity to adapt. Low-regret interventions that integrate existing community adaptive practices, engage with farmers’ needs and prioritise extension support may encourage more desirable counteractions to drought; however, further research is needed to establish the role of such interventions.
Keywords: Drought risk management; Financial compensation; Vulnerability; Adaptive capacity; Crop insurance